PERAN WORLD HEALTH ORGANIZATION (WHO) DALAM UPAYA PENANGANAN HIV/AIDS DI INDONESIA TAHUN 2010-2013 - Monalisa Putri; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This reseach describes the role of the World Health organization in haldling the spread of the HIV / AIDS outbreak in Indonesia. the rapid rise of HIV/AIDS cases in Indonesia, until 2013. The World Health Organization has declared an emergency on the international health situasion HIV / AIDS outbreak in Indonesia with the implementation of the program of the World Health Organization Global Programme on AIDS. Based on these issues, the problem is formulated as follows: "What is the role of WHO in efforts to address HIV / AIDS in Indonesia in 2010-2013?". World Health Organization asked all authorities to Participate The Necessary taking action to Prevent HIV/AIDS. This study Applies qualitative research method with library research. The sources of data are from the Journals, Books and the internet. this study uses the role of international organizations theory and non-state level of analysisThe research shows that the World Health organization has an important role in handling outbreaks with HIV/ AIDS in Indonesia, Especially in Indonesia. Through policy and strategy shape the draft strategy plan to eradicate an outbreak of HIV / AIDS, the World Health Organization urgent international cooperation to improve health facilities and treatment of diseases in countries affected with HIV / AIDS.Key words, the world health organizatin, shape strategy, foreign policy.